QUERY ANSWERING SYSTEM OF SHAHIH HADITH MUTTAFAQUN â€˜ALAIH USING INDONESIAN THESAURUS BASED ON QUERY EXPANSION AND NAÃVE BAYES CLASSIFIER - Rounaqi, Muhammad Fairuz Zumar; Crysdian, Cahyo; Melani, Roro Inda (Department of Informatics Engineering, 2020)
Abstractâ€” Hadith are all the words, deeds and provisions of the Prophet Muhammad SAW that are used as the second of Islamic law after Al-Quran. The purpose of this study is to make an Information Retrieval system called the Query Answering System is expected to facilitate users in searching and finding the hadith documents as the user's needs. This study implements the NaÃ¯ve Bayes Classifier method combined with Indonesian thesaurus as a query expansion to find the hadith documents that relevant to the input query. Based on the testing of 50 query data, the test results show that the use of query expansion gives better results than without using query expansion. Where based on testing of the top 1 data without using query expansion obtained an average recall value of 62%, an average precision value of 62%, an average accuracy value of 92.4% and an average value of the f-measure of 62%, while testing using query expansion obtained an average recall value of 66%, an average precision value of 66%, an average accuracy value of 93.2% and an average f -measure value of 66%. Based on the test results, the use of query expansion shows an improvement in the average recall value of 4%, an improvement in the average precision value of 4%, and an improvement in the average accuracy value of 0.8% and an improvement in the average f-measure value of 4% compared on without using query expansion.Â Index Termsâ€”hadith, information retrieval, query expansion, naÃ¯ve bayes.Â